NATO's About-Face: Adaptation to Gender Mainstreaming in an Alliance Setting. Issue 1 (28th November 2019) - Hardt, Heidi; von Hlatky, Stéfanie
Abstract: Scholars in global security studies have only recently focused attention on how and why international security organizations (ISOs) adapt. Since the United Nations Security Council's issuance of Resolution 1325, some ISOs have enacted changes to implement gender mainstreaming. The concept involves incorporating gender-based analyses in policy and planning and increasing women's representation. Drawing on interviews with seventy-one elites and a dataset of ninety-seven NATO gender guidelines, this article introduces an original argument for why NATO adapted to gender mainstreaming. Such adaptation is surprising given the military's historical resistance to gender considerations and that civilian bodies typically enact reforms. Findings indicate that other ISOs were substantially influential in the process and that institutional incentives built into NATO's military bodies drove military officials to implement mainstreaming in practice. Additionally, military elites perceived a link between gender mainstreaming and operational effectiveness, which further consolidated organization-wide adaptation. This study challenges long-held assumptions about militaries' resistance to gender-related changes. It also offers one of the first empirical assessments of gender mainstreaming in an ISO.